Memahami Konstruksi Nalar Epistemologi Etnik: Sebuah Kajian Filosofis - Elvy Maria Manurung; Yohanes Slamet Purwadi; Ignatius Bambang Sugiharto (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
In the 21st century, due to its incessant auto-criticism, the orientation of science is split into two. On the one hand, the monolythic tendency of positivism -with its physicalistic paradigm- is still prevalent. On the other, the tendency of openess toward the complexity of reality is also thriving. The latter would include the openess toward non physical variables or even toward esoteric experience. At this junction, the concept ofethnoepistemology is worth considering. With regard to this, this article seeks to see the fundamental differences between the universal-scientific epistemology and ethnoepistemology. Ethnoepistemology is examined in terms of its local ontological-worldview, which mostly is spiritual in character. It was found out that the local worldview generates a particular knowledge, with specific logic, method and vocabulary of its own. Complemented with some case-studies, the article comes up with the idea that the mistery of the world can be accessed from many points of view, resulting in different kinds of knowledge. That said, while scientific epistemology is not the only possible one, ethnopistemology can upgrade itself by learning from the work-ethos of scientific epistemology. Key words: episteme, worldview, logic, interdependency, holistic, experiential